Analysis of Factors Affecting Transaction Balance Discrepancies and Cashiers (Case Study at PT. Pos Indonesia Kota Bahagia) - Putra Agung; Rimal Mahdani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
As a company that serves financial transactions directly with customers, the accuracy and reliability of the cashier system is very important for PT. Pos Indonesia (Persero) in maintaining customer trust and the company's financial integrity. This research was conducted at PT. Pos Indonesia Happy City. This research is a descriptive qualitative type. The research object used in this research is PT. Pos Indonesia Happy City. The data collection method used in this research includes three methods, namely documentation, observation and interviews. The research results stated that the balance differences that occurred at PT. Pos Indonesia Happy City is caused by two factors, namely humans and system failure. The methods used to overcome this problem are identifying differences, reconciling transactions, re-verifying transactions, reporting findings, corrections and adjustments, evaluation and prevention, further action.